Percutaneous radiofrequency ablation of renal tumours: 29-month mean follow-up results of 118 patients - Ulys, Albertas; Žalimas, Algirdas; Merkytė, Rūta; Selickaja, Sandra; Trakymas, Mantas (Acta medica Lituanica, 2014)
Background. Percutaneous radiofrequency ablation (RFA) is a minimally invasive method of treatment based on thermal effects. This retrospective study aimed to clarify percutaneous RFA of kidney tumors – performance, extremeness and 5-year survival in patients with small renal tumors in a single center. Materials and methods. Between September 2003 and December 2012, a total of 118 patients underwent percutaneous RFA of renal tumors. During more than 9 years period 144 RFA procedures were performed. Tumors were verified by biopsy. We used 3 RFA techniques: RFA under ultrasound control only (US), ultrasound guided RFA with CT navigation (US/CT) and ultrasound guided RFA with CT navigation, fiducial markers placed around the kidney tumor before the treatment (US/CT/FM). RFA electrodes were one and three. Patients were followed up regularly by CT with contrast enhancement. Results. The mean patient age was 68.72 years (range 28 to 86). The mean tumor size was 2.8 cm (range 1 to 5.4). The mean follow-up time was 29 months (1–111 months). Radical dependence on technical procedures: only US 39 (66.1%), US/CT 18 (94.7%), US/CT/FM 37 (92.5%), p = 0.001. Radical differences between using one and three electrodes: 39 (66.1%) and 55 (93.2%), p